KONSEP NIFĀQ DALAM TAFSIR MODERN(Studi Komparatif Penafsiran ʿAlī al-Ṣābūnī Dan Wahbah al-Zuḥaylī) - Fiqri Nur Aulia Rahmi; Ghozi Mubarok (AL-BAYAN INSTITUTE, 2024)
The meaning of nifaq in the Qur'an must be interpreted deeply, broadly and in detail. Moreover, the meaning regarding a person's characteristics helps in practicing the contents of the Qur'an to the maximum. Discussions and debates of modern commentators about nifaq have several differences. This study will discuss the definition of nifaq and its characteristics according to the two commentators, namely Muhammad ʿAlī al-Ṣābūnī and Wahbah al-Zuḥaylī and how the similarities and differences between the two commentators regarding the definition of nifaq and its characteristics. The research method used is library research, in collecting data using the documentation method. while in analyzing data using descriptive analytical and comparative methods, the selection of verses focuses on verses that discuss nifaq. The results of the study can be concluded that the interpretation of the two commentators on the concept of nifaq has three conclusions, including: First, the definition of nifaq, Al-Ṣābūnī and Al-Zuḥaylī put forward the same opinion, namely nifaq are those who display faith and hide disbelief. Second, regarding the characteristics of nifaq, it can be concluded into two forms of nifaq, namely Al-nifaq al-i'tiqadi, including: deceiving and forgetting Allah, hesitating and doubting in faith, pretending to believe and al-nifaq al-'amali, including: lying (lying), ordering evil, forbidding good, Third, the comparison between the interpretations of Al-Ṣābūnī and Wahbah Al-Zuḥaylī on the concept of nifaq shows more similarities than differences, but the details of the differences are not substantial.